THE DEVELOPMENT OF INTELLIGENT TRANSPORT SYSTEM (ITS) FOR SPEED MANAGEMENT BASED ON DRIVER BEHAVIOUR (Case Study: Pekanbaru) - , RIZKI AMELIA, Prof. Dr. Ir. Siti Malkhamah, M.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The higher the speed, the shorter the available time to prevent collisions, and the more severe are the results of a collision. Posted speed limits contribute to reducing speed variability by establishing an upper bound on speed where the objective is to reduce the probability and outcome severity of accidents. Many drivers exceed the posted speed limit. The reasons for speeding are diverse and may relate to temporary motives e.g. being in a hurry, to more permanent personality characteristics e.g. risk taking, to human perceptual skills and limitations, as well as to characteristics of the road, the road environment and the vehicle. This research is to determine the reasons for speed limit violations in Pekanbaru. Then it tries to provide the solution related to ITS. Collecting data is carried out by using questionnaire. For the reasons of speed limit violations, the question is a type of likert scale. The population on this research covers up drivers with the minimum age of 17 years old because everybody who has already been 17 years old is deemed competent by the law and considered able to understand traffic signs when driving a vehicle. Rank analysis and factor analysis are used to achieve the research objectives. Rank analysis is used to determine the main reasons why drivers violate the speed limit, while factor analysis is used to determine the grouping of those reasons to become a simple factor. The 13 reasons of driversâ violating the speed limit, 5 main reasons are obtained. They respectively are in hurry condition, absence of traffic police, time is more important than safety, ignorance to speed limit signs and lack of concern to be intercepted by police. The factor analysis offers three simple factors why drivers violate the speed limit. Factor 1 considers to account for reasons to speed related to egocentric behaviour of the driver, factor 2 considers to account for reasons to speed related to passiveness of speed limit factor both in term of signs and police